POLA PENIJAHAN UDANG AIR TAWAR Macrobrachium sintangense De Man: PENGAMATAN SEMUSIM DI RANU KLINDUNGAN PASURUAN - Bambang Irawan; Indinah Indinah; Hani Sudarmanto (The East Java Biological Society, 2000)
The spawning pattern of Macrobrachium sintangense (de man) population in Klindungan pond (Ranu Klindungan) was observed. The number of eggs carrying female was count and high proportion of these female was found in August and February. This result indicate that there was two period of spawning in this population.